Energy storing carbon concrete heating element with phase change material for integration into smart home systems - Gliniorz Ralf; Lindner Marco; Gelbrich Sandra; Funke Henrik (MATEC Web of Conferences)
Securing and storing energy is one of the most important issues for the future of the global construction industry. Numerous technological innovations are being developed to meet this challenge. Every person has an individual consumption for private or commercial use. For example, a lot of energy is needed to build and operate a building. For this, it is necessary to develop technologies to secure and store energy in some way. This paper reports on the path to a new energy-storing carbon concrete heating element, the required flowable concrete mixture and the influence of the Phase Change Material (PCM) on energy storage, strength and producibility. The manufacturing process is semi-automated and virtual controlled by an online order generator. For example, a special mechanism for contacting the tailored meander-structured carbon roving and the automated messenger for several production steps have been created. All components used in this formation are suitable for Smart Home applications in modern houses, which can be implemented completely or as an isolated application with appropriate digital interface. Combined with presence recognition and artificial intelligence for lifestyle habits, these houses will be able to efficiently distribute rare and precious energy to where it is needed.